Edukasi Kesehatan Pencegahan Stunting Melalui Media Kalender: Health Education for Stunting Prevention Through Calendar Media - Djamaluddin, Nurdiana; Vidya Avianti Hadju (Universitas Muhammadiyah Palu, 2024)
Stunting is a condition where a child's physical growth and development are hindered due to a long-term lack of adequate nutritional intake. It is not just a physical issue, but also a health and developmental problem that involves various social, economic, and environmental factors. Inaccurate knowledge of mothers is the earliest cause of malnutrition in children. There are various types of media that can be used to maximize message delivery, such as print media, electronic media, billboard media, and entertainment media. One of the print media used for message delivery is educational calendars. Additionally, calendar media can contain many images and texts, is easy to understand, and can be placed in accessible areas where it can be read at any time. The aim of this community service activity is to enhance public knowledge on the prevention and improvement of nutrition for stunted toddlers. After the community service was conducted, there was an increase in public knowledge following the education provided about stunting through calendar media. After the counseling, the majority of participants understood how to prevent stunting, recognize stunting, and the impacts of stunting.